Graphene derivatives-based electrodes for the electrochemical determination of carbamate pesticides in food products: A review - Saqib, Muhammad; Solomonenko, Anna N.; Barek, Jiří; Dorozhko, Elena V.; Korotkova, Elena V.; Aljasar, Shojaa A. (Analytica chimica acta)
Graphene (GR) composites have great potential for the determination of carbamates pesticides (CPs) by electrochemical methods. Since the beginning of the 20th century, GR has shown remarkable promise as electrode material for various sensors. The contamination of food products with harmful CPs is a major problem as they do not always damage human health immediately, but can be harmful after prolonged exposure. A range of advantages can be gained from their electrochemical determination, such as high sensitivity, reasonably selectivity, rapid detection, low limit of detection, and easy electrode fabrication. Furthermore, these electrochemical techniques are robust, reproducible, user-friendly, and conform to both “green” and “white” analytical chemistry. This review is focused on results published in the last ten years in the field of electrochemical determination of CPs in food products using GR and its derivatives.